The Effect of Team Affective Tone on Team Performance: The Roles of Team Identification and Team Cooperation - Chieh‐Peng Lin; Hongwei He; Yehuda Baruch; Blake E. Ashforth (2016)
Affective tones abound in work teams. Drawing on the affect infusion model and social identity theory, this study proposes that team affective tone is related to team performance indirectly through team identification and team cooperation. Data from 141 hybrid‐virtual teams drawn from high‐tech companies in Taiwan generally supported our model. Specifically, positive affective tone is positively associated—while negative affective tone is negatively associated—with both team identification and team cooperation; team identification is positively associated with team cooperation; and team cooperation is positively associated with team performance. Managerial implications and limitations are discussed. © 2016 Wiley Periodicals, Inc.